Aplicação da competência de comunicação em projetos como base para uma proposta de um projeto educacional em uma instituição de ensino superior - Amaral, Iraides Gonçalves do (2013)
This dissertation investigated the use of communication competence in projects specifically focused on educational project. This investigation is justified by reason of changes occurring in the contexts of teaching and learning, which implied the need to understand how the characteristics of today's students require revitalization of these contexts. Aiming to address this need, this dissertation was to understand how communication competence in projects can be used in an educational project in higher education institutions in management, by investigating the appropriateness of the application communication competence in an educational project. For such, was adopted a qualitative approach, data were collected through: a survey with 1.161 students; indirect and non-participant observation, with respect to the part recorded in observation protocol totaling one-time 3,570 minutes, the computed 51 times the number was assisted multiplied by 70 minutes in length and semi-structured interview with the producer of the play, the actors, teachers and coordinators of the educational institution in which students are embedded interview. The analysis of data from those sources of evidence was conducted through of the content analysis. The results pointed the relevance of the application of communication competence in the educational project studied. The additional contribution of this paper resides in the proposition of an educational project under the aegis of teaching and learning, research and extension, with the use of scenic art.